As casas subterrâneas e sua paisagem: cartografando o ambiente - Novasco, Raul Viana (Universidade do Vale do Rio dos Sinos, 2013)
Linguistic and ethnographic studies report that Southern Jê, whose origin dates back to the central Brazilian plateau, have started their migration towards the southern highlands of Brazil by approximately 3.000 years ago. The moment they arrive to the highlands of Santa Catarina is still unknown, however, it is clear that throughout the process of occupation undertaken of the southern Brazilian plateau, the Southern Jê maintained a very close relationship with the environment, perceiving climate change and especially changes in the composition of biotic region (fauna and flora), developing adaptive responses to natural transformations, and transforming their social organization. Based on these assumptions, the present work was developed with the aim of capturing elements that allow us to identify adaptation and settlement strategies developed by these groups in the area of the site Rincão dos Albinos. The archaeological site Rincão dos Albinos is situated in the municipality of São José do Cerrito, dissected plateau in the State of Santa Catarina, in the drainage area of the watershed of the Canoas River. The site consists of 107 pit houses, arranged in an area of 200 meters radius and dates obtained inside and outside of residential structures suggest that the occupation had its beginnings at 1400 B.P., a period that the plateau of Santa Catarina is mostly covered by campos intersected by rivers and streams accompanied by small araucaria forests. Thematic maps were produced in various scales and present specific data from the site, such as the distribution of structures and their relations with the space where they are inserted, and regional geographical features, including the middle course of the Canoas River. The maps allowed us to make a wider reading of the space where the site is located, and associated with the analysis of paleoenvironmental, geographic, ecological and cultural dates, made us realize that the archaeological site Rincão dos Albinos - in its layers of occupation and landscape - records at least two periods of cultural and environmental transition.
Keywords: Jê Meridional; Casa subterrânea; Arqueologia do planalto; Rincão dos Albinos; Paleoambiente; Arqueologia; Southern Jê; Pit houses; Archaeology of the plateau; Paleoenvironmental; Archaeology; ACCNPQ::Ciências Humanas::História